Utilizing usability evaluating model in applying CMM to improve. - Mohamed Talib, Amir; Abdullah, Rusli (Canadian Center of Science and Education, 2010)
Maintenance plays an important role in the life cycle of a software product. It is estimated that there are more than 100 billion lines of code in production in the world. As much as 80% of it is unstructured, patched and not well documented. Maintenance can alleviate these problems. The purpose of this paper is to explore the use of the Capability Maturity Model (CMM) to improve the quality of software maintenance process (SMP). The architecture of the CMM model has been retained almost as is while its content, which was specific to the development process, has been either modified or extende d to take into account the characteristics specified to the maintenance function, these characteristics were th en organized into key process areas (KPAs) of CMM model. This paper applied the definition of (ISO 9241-1 1, 1998) that examines effectiveness, efficiency, and satisfaction. The emphasis will be given to the SMP activities